EKSISTENSI ADVOKAT DALAM MEMBERIKAN BANTUAN HUKUM KEPADA MASYARAKAT TIDAK MAMPU - Huda, Samsul (STIH Zainul Hasan Kraksaan Kraksaan, 2023)
ABSTRACT Legal aid is an effort to provide access to people who are financially incapacitated or have limited access to justice and their rights before the law. Provision of legal aid is an important matter in law enforcement for poor people. The state has a role and responsibility in providing legal aid either directly or through designated institutions, such as legal aid or public advocacy agencies. Provision of legal assistance to underprivileged communities is very important to ensure that the rights of underprivileged communities are properly protected before the law. This study aims to determine the mechanism of providing legal aid to the poor and the forms of existence of advocates in providing legal aid. This research is an empirical legal research located at the Legal Aid Post Office of the Indonesian Advocates Association at the Kraksaan District Court. The results of this study indicate that the mechanism for providing legal aid at the IKADIN Legal Aid Post Office at the Kraksaan District Court is very open to the poor. Beginning with submitting a written application containing at least the applicant's identity and a brief description of the subject matter for which Legal Aid is being requested, submitting documents relating to the case and finally attaching a statement of incapacity from the lurah, village head or equivalent official at the place of residence legal aid applicant. If all the requirements have been completed, then the implementation of legal aid for a poor or incapacitated defendant can be held. Key Words: Legal Aid, Advocate, Community